As metodologias ativas na prática de docentes do ensino profissional - Souza, Alessandra Martins (2017)
This research had the objective of investigating the teacher formation and the establishment of the Know-how of teachers of Profession Education (EP), for the use of Active Methodology (MA) in the classroom. The objective is to research on a constitution of know-how and setting up of such professionals, for the use of MA. The research problem focused on educational formation of these teachers and if it can offer them subsidies to develop works with MA in the classroom. We conducted a qualitative research with the participation of teachers from a Technical School (ET), located in the Municipality of São Paulo and maintained by Paula Souza Center (CPS). For a data collection, we used an open-ended questionnaire, analysis of the training of professionals and their knowledge and use of MA. Through bibliographical research, we established a theory in the studies of Antonio Nóvoa (1991, 1992, 1999), Ivor Goodson (1992), Maurice Tardif (1999, 2000, 2002, 2003), Selma Garrido Pimenta (1993), authors who deal with the constitution of theoretical and practical knowledge of professors and contributions of Paulo Freire (1996, 2006), whose works show the MA and the problematization as driving forces of education and training of critical and reflexive subjects. The relevance of this research is related to the importance that has been given to EP in the last decades, as a driver of the formation of the worker capable to meet the requirements of the labor market and the production system, as well as their capacity to mobilize skills that are part of everyday production, especially those that circumscribe themselves to the problem resolution, decision-making and the autonomy. EPs teachers are required knowledge that be able to propose working methods that privilege the reflection, the critical positioning, the autonomy and the search for knowledge, essential factors in the world of work. The results of the analysis of interviews and research bibliography has indicated that a traditional view of the EP in Brazil persists, as a consequence of the colonial heritage, a time when the learning of the craft was intended to the lower stratum of the population and masters was required the mastery of functions to teach learners. As a consequence, a training of teachers to act in the EP is justified in the belief that the know-how and setting up teachers necessary for practices are those acquired in a daily atmosphere of work and production, there is no need a scientific background. Consequently, the teachers' practices are sometimes, unintentional, improvised, empirical and dependent on trial and error, and formulas already tested by other teachers. This enables professionals deal with the curiosity, questioning, formulation of hypotheses made by students due to the face of a problem posed from the use of the MA in the classroom, generate situations that, well directed, would produce a more meaningful and contextualized teaching, able to develop the reflexion, criticality, autonomy and the protagonism of these students